High protein intake in human/maternal milk fortification for ≤1250 gr infants: intrahospital growth and neurodevelopmental outcome at two years - Biasini, Augusto; Monti, Fiorella; Laguardia, Maria Chiara; Stella, Marcello; Marvulli, Lucia; Neri, Erica (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the study: Extrauterine growth restriction and failure to thrive remain a major problem in Extremely Low Birth Weight infants. Nutritional support in preterm babies has the objective to improve the achieve rate of growth similar to those of the fetus in utero at the equivalent gestational age. The aim of the study was to evaluate feeding tolerance, intrahospital growth, neurological outcome and anthropometric data until 24 months of corrected age (mca) from different protein intake assumed by preterm babies